Information and communication technologies in tourism 2014 : proceedings of the international conference in Dublin, Ireland, January 21-24, 2014 - Tussyadiah, Iis (Springer International Publishing Imprint: Springer, 2013)
The papers presented in this volume advance the state-of-the-art research on social media and Web 2.0, electronic tourism marketing, website development and evaluation, search engine marketing and optimization, IT adoption and diffusion, virtual travel communities, mobile technologies, management information systems in tourism, eLearning, recommender systems for tourism businesses and destinations and electronic distribution for hospitality and travel products. This book covers the most significant topics contributed by prominent scholars from around the world and is suitable for both academics and practitioners who are interested in the latest developments in e-Tourism.